nataliekedwards04
nataliekedwards04
04-09-2020
Mathematics
contestada
Solve 3(2 – c) = – (c + 4).
Respuesta :
muhammadolim
muhammadolim
04-09-2020
Answer:
c = 5
Step-by-step explanation:
[tex]3(2-c) = -(c+4)[/tex]
[tex]3\times 2-3\times c=-c-4[/tex]
[tex]6-3c=-c-4[/tex]
[tex]c-3c=-4-6[/tex]
[tex]-2c=-10[/tex]
[tex]c=5[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 82+ )
Otras preguntas
Finding the area of a regular polygon
accept verb Synonyms: receive, believe, undertake Antonyms: refuse, reject, defy Which word would be the best replacement for the underlined word in this senten
Please help, need for math hw and cant figure it out
48. Which of the following (a) KCI (b) NaCl is called Sylvine? (c) CaCl₂ (d) MgCl₂
Hiroshima, Japan was selected for what main reasons? It was a completely military target. It had already been heavily bombed so civilian casualties would be l
To heat up an undetermined volume of water from 20 degrees to 50 degrees takes 5 minutes. What is the heating factor of the element used to heat up water?
x6 = 64 solve for X please
PLEASE HELP IM STUCK ON THIS
we need food for _and _
The solutions that are used in this experiment have alcohols as both the solvent and the reactant. How is the excess alcohol removed?.